A DIDACTICAL DESIGN FOR TEACHING CONTINUITY OF FUNCTION - Tonra, Wilda Syam; Suryadi, Didi; Endang Cahya Mulyaning; Kusnandi; Hadi, Windia (IAIN Ambon, 2024)
Students face significant difficulties in understanding the continuity of functions that produces learning obstacle. Therefore it is necessary to develop a didactical design to enhance the teaching process. Qualitative research in this study is Didactical Design Research (DDR). This study was conducted in Universitas Khairun. Participants consist of two groups of students. Data collection and analysis 1) Test in which the results of this will be analyzed descriptively 2) In-depth interviews guideline in this research was to confirm students' answers 3) A didactical design which is used to minimize the obstacle. The results show that the Initial learning obstacle is the student cannot choose which function to use to find the left and right limit values, the student knows well the 3 conditions for continuity of function, however, the student incorrectly solves the problem. There are also the students who didn't know the conditions for continuity of function 2) Didactical design is compiled based on Theory of Didactical Situation (TDS) 3) The impact of implementing the didactical design can provide an understanding of continuity of function, there are still learning obstacles that arise. Further research is needed to ensure that as few learning obstacle appear as possible. Keywords: Continuity of Function; Didactical Design; Didactical Design Research (DDR)